Loss of function of folylpolyglutamate synthetase 1 reduces lignin content and improves cell wall digestibility in Arabidopsis. Issue 1 (December 2015) - Srivastava, Avinash; Chen, Fang; Ray, Tui; Pattathil, Sivakumar; Peña, Maria; Avci, Utku; Li, Hongjia; Huhman, David; Backe, Jason; Urbanowicz, Breeanna; Miller, Jeffrey; Bedair, Mohamed; et al.
Abstract Background One-carbon (C1) metabolism is important for synthesizing a range of biologically important compounds that are essential for life. In plants, the C1 pathway is crucial for the synthesis of a large number of secondary metabolites, including lignin. Tetrahydrofolate and its derivatives, collectively referred to as folates, are crucial co-factors for C1 metabolic pathway enzymes. Given the link between the C1 and phenylpropanoid pathways, we evaluated whether folylpolyglutamate synthetase (FPGS), an enzyme that catalyzes the addition of a glutamate tail to folates to form folylpolyglutamates, can be a viable target for reducing cell wall recalcitrance in plants. Results Consistent with its role in lignocellulosic formation, FPGS1 was preferentially expressed in vascular tissues. Total lignin was low infpgs1 plants leading to higher saccharification efficiency of the mutant. The decrease in total lignin infpgs1 was mainly due to lower guaiacyl (G) lignin levels. Glycome profiling revealed subtle alterations in the cell walls offpgs1 . Further analyses of hemicellulosic polysaccharides by NMR showed that the degree of methylation of 4-O -methyl glucuronoxylan was reduced in thefpgs1 mutant. Microarray analysis and real-time qRT-PCR revealed that transcripts of a number of genes in the C1 and lignin pathways had altered expression infpgs1 mutants. Consistent with the transcript changes of C1-related genes, a significant reduction inS -adenosyl-l -methionine content was detected in thefpgs1 mutant. The modified expression of the various methyltransferases and lignin-related genes indicate possible feedback regulation of C1 pathway-mediated lignin biosynthesis. Conclusions Our observations provide genetic and biochemical support for the importance of folylpolyglutamates in the lignocellulosic pathway and reinforces previous observations that targeting a single FPGS isoform for down-regulation leads to reduced lignin in plants. Becausefpgs1 mutants had no dramatic defects in above ground biomass, selective down-regulation of individual components of C1 metabolism is an approach that should be explored further for the improvement of lignocellulosic feedstocks.